Patterns of Indigenous Knowledge in Reproductive Health: A Study in Himachal Pradesh - Singh, Kiran (International Journal of Social Sciences and Management, 2015)
In the Present era various populations of India have belief in every phase of life sickness. Indigenous knowledge cannot be verified by scientific criteria nor science can be adequately assesses tenets of Indigenous knowledge. Both built on different philosophy, methodology and criteria. These two systems tends to serve contrast exploration of interface. Indigenous knowledge for health concepts articulate physical activity, spiritual emotional element from both individual and communal perspective. Objective: To explore once to indigenous medicine, health local healer. To explore practice used by people during pregnancy discomfort dietary practice source of healing. Area of Study: Himachal Pradesh Village Population Study: Brahmins. It was observed that curing different discomfort during pregnancy women’s are using different local plants. DOI: http://dx.doi.org/10.3126/ijssm.v2i2.12285 Int. J. Soc. Sci. Manage. Vol-2, issue-2: 139-142